Uso de la torta de semilla de algodón en raciones balanceadas para cerdos en proceso de crecimiento - Braham, J.E.; BRESSANI, R; Escobar, N. E; Aguirre, A. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
An experiment was conducted with Duroc-Jersey weanling pigs to determine the percentage of cottonseed oil meal that could substitute all the sesame oil meal in a simplified swine ration composed of Guatemalan feedstuffs. Cottonseed oil meal substituted 0, 5, 10, 15, and 20% of the sesame oil meal of the basal ration. Weight gains and feed efficiency were very satisfactory when the rations contained up to 15% of cottonseed oil meal. Higher levels resulted in toxic symptoms characterized by thriftiness, anorexia, diarrhea and dry, scaly skin. The free gossypol contributed by the cottonseed oil meal was calculated to be 0.0000, 0.0035, 0.0070, 0.0100, and 0.0140 g/100 g of the diets. The cost per pound of live pig, was around US$0.12, 0.11, 0.11, 0.13 for rations 1, 2, 3, 4 and 5, respectively.